2012
DOI: 10.1016/j.fct.2012.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged consumption of flaxseed flour increases the 17β-estradiol hormone without causing adverse effects on the histomorphology of Wistar rats’ penis

Abstract: Consumption of foods rich in phytoestrogens such as flaxseed has increased due to its chemoprotective effects, especially those related to the cardiovascular system. The flaxseed has components that can interfere with development of male reproductive system. This study aims to investigate the possible effects of prolonged consumption of flaxseed flour on hormonal and histomorphologic penis parameters of adult Wistar rats. Rat dams were divided into two groups during lactation period: the control group that was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Pan et al, evaluated the effects of purified forms of daidzein and suggested that daily exposure of young male rats to phytoestrogens may result in the impairment of penile erection during adulthood. In a study similar to the present one, Cardozo et al (2012), observed that the prolonged consumption of flaxseed meal does not alter penile development. Exposure to purified forms of phytoestrogens does not mimic the metabolic interaction that occurs in the body.…”
Section: Discussionsupporting
confidence: 59%
“…Pan et al, evaluated the effects of purified forms of daidzein and suggested that daily exposure of young male rats to phytoestrogens may result in the impairment of penile erection during adulthood. In a study similar to the present one, Cardozo et al (2012), observed that the prolonged consumption of flaxseed meal does not alter penile development. Exposure to purified forms of phytoestrogens does not mimic the metabolic interaction that occurs in the body.…”
Section: Discussionsupporting
confidence: 59%
“…This result explained by DeVore and Scott (2012) who stated that CYP17 is a key enzyme in the steroidogenic synthesis pathway. Moreover, Cardozo et al (2012) observed an increase in estradiol after a prolonged Advances in Animal and Veterinary Sciences intake of 25% flaxseed. Furthermore, Corrêa et al (2017) found that the prolonged exposure to flaxseeds induced a significant increase in serum estradiol levels in rat.…”
Section: Effect Of Linseed Oil and Fluconazole On Lh Receptor (Lhr) A...mentioning
confidence: 94%
“…In contrast, Ward et al (2001) noticed no effects of flaxseed exposure, diet with 10 per cent flaxseed flour, during lactation only or during lactation and post-weaning in male and female offspring on the reproductive indicators analysed (anogenital distance, onset of puberty, oestrous cycle time and uterus, ovary, prostate and testis relative weight). Cardozo et al (2012) investigated the possible effect of maternal intake of flaxseed during lactation by dams and post-weaning by the offspring on the hormonal and histomorphological parameters of the penile of adult rats (250 days), and noticed that when compared to control group, the offspring had higher concentrations of 17b -oestradiol. Also, with respect to penile histomorphometry, these animals had lower total spongy body area values.…”
Section: Effects On Lipid Profilementioning
confidence: 99%